A Collaborative Psychiatric-Genetics Inpatient Care Delivery Model Improves Access to Clinical Genetic Evaluation, Testing, and Diagnosis for Patients With Neurodevelopmental Disorders - Shillington, Amelle; Lamy, Martine; Dominick, Kelli C.; Sorter, Michael; Erickson, Craig A.; Hopkin, Robert (Frontiers in Genetics, 2022)
Neurodevelopmental disorders including autism spectrum disorder, intellectual disability and global developmental delay are among the most common indications for referral to clinical genetics evaluation; and clinical genetic testing is indicated for people with neurodevelopmental disorders. There are known barriers to care in accessing clinical genetics evaluation for this patient population. We created a collaborative psychiatric-genetics consultation service and psychiatric-genetics outpatient clinic with the goal to improve care delivery to patients with neurodevelopmental disorders. Two years after the launch of this pilot program, our data demonstrates improved access to genetics evaluation with shorter wait times, and fewer patients lost to follow up. Perhaps most importantly, new genetic diagnoses changed medical care for the majority of patients who received a new diagnosis.